PENGEMBANGAN SISTEM INFORMASI PENGELOLAAN KEGIATAN MASJID AL-FALAH SURABAYA - Yusron Andrian; Dhiani Tresna Absari; Fitri Dwi Kartikasari (CALYPTRA, 2018)
Masjid Al Falah Surabaya is one of the places of worship for Muslim religion in Surabaya. The mosque has divisions to manage activities associated with the mosque. The division is among others division of dakwah ibadah, division of zakat infaq, secretarial division, qurban committee, and others. Division of dakwah ibadahis a division that manages the study activities. Activities undertaken by the division of dakwah ibadah there are monthly reports and there are no monthly reports. Activities that have monthly reports are routine activities carried out by the division of dakwah ibadah, namely Sholat Rawatib, Kajian Spirit Muslim Sukses, Kajian Maghrib, Kajian Subuh, dan Kajian Majelis Jejak Nabi. Other activities or incidental activities do not have monthly reports. This matter may cause division of dakwah ibadahnot knowing what incidental activity has been done and enthusiasts from such activity.In addition to the division of dakwah ibadah, zakat infaq division also has difficulties in receiving zakat infaq recorded in paper form. So also with the qurban committee in performing receipt qurban recorded in the paper each acceptance. While the difficulties experienced in the secretarial division is to know the progress of incoming mail. The existing difficulties can be solved by establishing an activity management information system. This information system is made using system theory, information, management, management information system, and mosque organization. Once this information system is created, a trial is conducted to ensure that the information system is error-free and can be used in accordance with the objectives of the information system.